Investigação teórica sobre possíveis aplicações na eletrônica de nanofios de AlN, GaN e InN: um estudo de primeiros princípios - Colussi, Marcio Luiz (2012)
Using the formalism of Density Functional Theory with spin polarization and the Generalized Gradient Approximation for exchange and correlation term, we studied the stability and electronic properties of substitutional impurities of C, Si and Ge in GaN, AlN and InN nanowires and the variation of the band offset with the diameter variation in AlN/GaN nanowires heterojunctions. For the study of substitutional impurities we use AlN, GaN and InN nanowires in the wurtzite phase with diameter of 14.47 Å, 14.7 Å and 16.5 Å, respectively. For the study of variation of the band offset with the diameter of the nanostructure, we use nanowires in the wurtzite phase with a mean diameter ranging from 0.99 nm to 2.7 nm and the zinc blende phase with an average diameter ranging from 0.75 nm to 2.1 nm. The electronic structure calculations show that of GaN, AlN and InN nanowires are semiconductors with direct band gap at point Γ. To study the substitutional impurities, we consider that the impurity can occupy the cation or anion sites in non-equivalent positions that are distributed from the center to the surface of the nanowire. For the C impurities, in GaN nanowires, we find that when the C atom is substituted in the N site, it will be uniformly distributed along the diameter of the nanowire. When substituted at the Ga site, it will be preferably find on the surface of the nanowire. In this case, the formation energy of CGa is almost identical to the CN, thus can occur formation of the auto-compensed CN-CGa pair. In AlN nanowires, when the C atom occupying the N site, it is also observed an almost uniform distribution along the diameter of the nanowire with a small preference (less energy formation) to the surface sites. Since the formation energy of the CN is lower than CAl in all regions of the nanowires, taking thus more likely to form CN. For InN nanowires, in the center sites, the formation energy of the CN and CIn is very similar, and the CN will have a uniform distribution along the diameter, but on the surface of the CIn is more stable and band structure show that this configuration has shallow donor levels. For Ge substitutional impurities in GaN nanowires, we observed that the center of the nanowire, the Ge atom is more likely to be found located in the Ga site, but in surface to find the most likely of N site, this being the most stable configuration. For AlN nanowires, the center of nanowire is possible to find the Ge atom at the N or Al sites, as the formation energy is practically the same. On the surface the more likely it is to find the Ge atom of the N site, which also is the most stable configuration. As for InN nanowires, the Ge atom will be found preferably at the In site with uniform distribution along the diameter of the nanowire. Analyzing the band structure of GeIn observed shallow donor levels. For the Si substitutional impurities, we obtain that in GaN and InN nanowires of the most stable configuration, the Si atom is to be found at the cation (Ga and In) sites in the central sites of the nanowire and analyzing the band structure of SiGa and SiIn, we also observed shalow donor levels. However, for AlN nanowires in the centerof the nanowire is greater the probability of finding the Si atom at the Al site, but the surface is greater the probability of finding the Si atom at the N site which is the most stable configuration. Finally, we analyze the variation of the band offset to the change in diameter of the nanowires forming the heterostructure. We consider heterostructure on yhe wurtzite and zinc blende phases, therefore during the synthesis the two phases are obtained. We found that the result is similar for the two phases and the extent that the diameter increases the value of the band offset also increases, tending to the value obtained for the bulk.